A wireless buckle transducer for measurement of human forearm tendon tension: operational principles and finite element study - Rastegarpanah, Alireza; Taylor, Stephen J. G. (Frontiers in Bioengineering and Biotechnology, 2024)
Conventional methods for evaluating the management of spasticity, a complex neuromuscular disorder, typically fail to directly measure the muscle forces and loads applied through tendons, which is crucial for accurate diagnostics and treatment. To bridge this gap, we developed a modular buckle transducer (BT) to measure muscle force transmissions in vivo. This device adjusts to accommodate tendon sizes ranging from 3 mm to 5 mm, maintaining accuracy within this range and avoiding needing identical tendon calibration. This study first presents the mechanical principles for determining the tendon tension T using several strain gauges appropriately positioned, allowing for varying angles of passage of the tendon through the device. Next, we present a finite element (FE) model that uses multiple linear regression to determine T while varying the tendon diameter and lateral placement within the device for several candidate strain gauge locations on the device baseplate. Finally, we propose several alternative ways of combining gauge strains. Initial simulation results demonstrated that this placement facilitates effective pre-implementation calibration, with the device accommodating human/equine tendon variations from 3mm to 5mm in diameter for a range of gauge placements. Future validation of this technology will involve direct testing on explanted human/equine tendons to verify the practical utility of the BT, aiming to establish a new standard for assessing and managing neuromuscular disorders like spasticity.